What can satisfy customers in servitization? Service or goods innovation - Xiao, Xiaohong; Zhou, Chengxu; Mao, Hongyi (The Journal of business & industrial marketing, 2023)
Purpose This study aims to investigate the impact of the two essential subjects of servitization (service and goods innovation) on customer satisfaction. The authors explained the paradox of servitization by determining how service innovation and goods innovation affect customer satisfaction interacting with environmental turbulence and marketing intensity. Design/methodology/approach The authors obtained 376 observations of 84 listed Chinese companies. On the basis of content analysis and measurement from secondhand data, the authors first tested the hypotheses in the fixed-effects model. The authors conducted a split-sample analysis by dividing environmental turbulence into two samples to explain the results effectively and better interpret the relationship between two innovations to customer satisfaction. Findings The results show that goods and service innovations positively affect customer satisfaction, but the effect of service innovation is more substantial. Furthermore, environmental turbulence negatively moderates the relationship between service innovation and customer satisfaction. The empirical results indicated that, if enterprises enhance marketing intensity, then the growth of environmental turbulence weakens the positive impact of goods and services innovation on customer satisfaction. Originality/value This study provided an understanding of the impact of servitization on intangible assets. This study also responded to previous literature’s call for research on the impact of external environmental factors on servitization.